Salt‐effect enhanced hollow‐fiber liquid‐phase microextraction of glutathione in human saliva followed by miniaturized capillary electrophoresis with amperometric detection. Issue 5 (8th January 2020) - Luo, Dan; Fang, Zhonghui; Zhao, Xiaoshuang; Ma, Yaolu; Ye, Jiannong; Chu, Qingcui
Abstract: A hollow‐fiber liquid‐phase microextraction (HF‐LPME) method was established for purification and enrichment of glutathione (GSH) in human saliva followed by a miniaturized capillary electrophoresis with amperometric detection system (mini‐CE‐AD). Based on regulating isoelectric point and increasing salt effect to modify donor phase, HF‐LPME could provide high enrichment efficiency for GSH up to 471 times, and the extract was directly injected for mini‐CE‐AD analysis. The salt‐effect enhanced HF‐LPME/mini‐CE‐AD method has been successfully applied to saliva analysis, and acceptable LOD (0.46 ng/mL, S/N = 3) and recoveries (92.7–101.3%) could be obtained in saliva matrix. The sample pretreatment of this developed method was simple and required no derivatization, providing a potential alternative for non‐invasive fluid analysis using portable instrument.